Peningkatan Akses dan Pemerataan Potensi Lembaga Pendidikan Islam - Yayuk Zulaikah; Sokip Sokip; Asrop Safi’i (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
The purpose of writing this article is to determine increased access and equal distribution of the potential of Islamic educational institutions. This research uses a type of library research. Library research is research carried out by reviewing various journals and related reference books. The results of his research show that one of the pillars of national education is the expansion and equal distribution of access to education. Expanding and equalizing access to education which is aimed at expanding the capacity of educational units by referring to the national priority scale which provides equal opportunities for all students from various groups of society who are diverse both socially, economically, gender, geographically and at the level of intellectual ability, and physical condition. Expanding and equalizing access provides the widest possible opportunities for the Indonesian population to be able to learn throughout their lives in order to increase the nation's competitiveness in the current era. Access to Islamic educational institutions has great significance for the development of individuals and society as a whole. This helps understand Islamic teachings, strengthens religious identity, teaches morals and ethics, understands relevant social and political issues, and helps build character and integrate religious values ​​in daily life. Obstacles to access to Islamic education in this village include Lack of material books and competence of teaching staff. This factor influences the quality of education and students' understanding of Islamic teachings. Therefore, to overcome this problem, greater efforts need to be made to increase access to education, provide adequate book materials, and increase the competency of teaching staff in village areas. Teacher training plays a key role in the distribution of Islamic religious education. Effective teacher training should focus on understanding local culture, relevant curriculum, innovative teaching methods, classroom management skills, community involvement, use of technology, and development of empathy skills.